O mito de Cassandra e outras vozes silenciadas - Herculano, Révia Maria Lima (2024)
The aim of this work is to research the myth of Cassandra, based on the works of Aeschylus and Eurípides, analyzing other female entities who are victims of divine power. We chose for research the works Agamemnon and The Trojan Women, tragedies that reveal the uniqueness of this myth. Cassandra, princess of Ilion, also a priestess of Apollo, despises the attempt at intimacy by the god who, rejected, punishes her with the curse of complex verbal communication, also causing her a confused state of mind, and for this reason she is considered crazy by her family and fellow citizens. The Trojan princess begins to experience trances and hallucinations. In this dissertation, we will address cases in which female entities become victims of their disobedience to the divine, which results in the duty of punishment and blame on the part of the divinity. We will also focus on the disobedience of Pandora, a Greek myth interpreted as a great evil and analogous to the biblical myth of Eve, narrated in Genesis; the nymph Echo silenced by Hera, wife of Zeus, a goddess who, jealous of Echo for hiding the nymphets who were with Zeus in the forest, punished her by making her always repeat the last syllables of the words she heard, preventing the muse from having friendly or romantic relationships. At the same time, a text that surprises us with its originality and that came to our hands at the end of the master's degree: Alexandra (Cassandra) monologue by Lycophron, 285 BC-246 BC, which preserves the oracular voice of the princess. In this guideline, we will define what myth is, also pointing out archetypes that translate the soul of the woman, actualized in images, which according to Jung, inhabit the feminine unconscious, emitting the energy that we certainly inherited biologically.